Estudo químico e biológico de Pseudobombax marginatum - Sousa, Anderson Freitas de (2020)
Popularly known as Embiratanha, Pseudobombax marginatum is a widely distributed species among biomes, exclusive to South America, which belongs to the Malvaceae family. In folk medicine it is used as an anti-inflammatory in the treatment of ulcers, gastritis and back pain. This study was conducted to identify and quantitate the polyphenolic compounds present in the methanol extracts of the bark, roots, leaves, flowers and fruit of P. marginatum, as well as to evaluate the antioxidant capacity, and in addition α-glucosidase and acetylcholinesterase inhibition. The individual constituents of the methanol extract were identified and quantitated by HPLC-UV. The antioxidant capacities of the samples were evaluated by the DPPH and hypoxanthine/xanthine oxidase assays. Inhibition of α-glucosidase and acetylcholinesterase enzymes of the methanol extracts was evaluated in vitro. Eight polyphenolic compounds were detected and quantified in methanol extracts from the various botanical parts of P. marginatum.The highest concentration of individual phenolics were 6-methoxyquercetin glucoside (87.20 g/kg) and procyanidin B2 (60.53 g/kg) in the leaf extracts. In the DPPH assay, the strong antioxidant capacity was evident in the methanolic extracts of the bark (IC50 = 2.1 ± 0.01 µg/mL). The hypoxanthine/xanthine oxidase assay confirmed most of the results obtained with DPPH. The lowest IC50 values ​​in relation to α-glucosidase inhibition were obtained for the bark (IC50 = 0.87±0.01 μg/mL) and leaf extracts (IC50 = 1.14±0.19 μg/mL). The hexane extracts of the leaves (12 mm) and methanol (10 mm) of the fruits indicated the most promising data of anticholinesterase activity. Methanol extracts of P. marginatum botanical parts may contribute to the formulation of effective drugs for the treatment of Type 2 diabetes. Further studies are needed on their extracts and their therapeutic action.